Fatores determinantes para o sucesso de startups de TI no Brasil: uma avaliação crítica - Cavalheiro, Cristian Mairesse (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation presents a critical assessment of the determining factors for the success of IT startups in Brazil. The world of startups has gained increasing worldwide interest for eager entrepreneurs in following the ways of the success of major players in technology that once beginners, began in a garage only with an idea and a lot of dedication. From the expression in English "start from the scratch", startups are companies that start from a different idea with potential to make money in a short time and low investment, that is, innovation with a high potential for profitability and scalability, but high risk. Although the technology startups with great market value have relevance in the economy, the factors that lead to their success are still unclear with few academic researches exploring the theme. As specific objectives the research identifies the economic, social and cultural basis references that influence the comparative factors of success and failure among some major innovation clusters in the United States and in Brazil, identifies the comparative factors of entrepreneurship in IT startups among some major innovation clusters in the United States and in Brazil, analyzes the main constraints faced by entrepreneurs in Brazil that result in major barriers to the growth of Brazilian IT startups and indicates strategies that can offer support to the investors regarding the viability of startups , increasing their chances of creating a great potential company in Brazil. A survey was conducted in the literature to identify the elements to be searched. The research presents a quantitative exploratory study field that approached 217 entrepreneurs from Brazil and a qualitative one with 37 people from the startup ecosystem, 9 of them from the United States and 28 from Brazil. In the United States the researcher visited the Silicon Valley and Boston area and in Brazil five innovation clusters were visited in Recife, Belo Horizonte, Porto Alegre and São Paulo. Data was grouped into analysis dimensions and the results have led to the following considerations: it was possible to identify a gap in the entrepreneurial education and in the role of the university in a greater integration with the corporate sector; in the government on the need of reducing bureaucracy of the public and private sector in improving basic infrastructure services; one of the most relevant factors of the research was the identification of the principal founder determination in pursuing the realization of the great dream and in the creation of the talent team, considering that his initial goal was not specifically to become rich; a difficulty of the Brazilian to use the capital for risk, as the cost in Brazil and cultural factors generate a high uncertainty degree about the return. Finally, although everything in Brazil is "too little, too late", there is widespread hope of generating highly successful startups in Brazil, that is, with a market value of more than $ 1 billion.
Keywords: Startups; Ecossistema ou clusters de inovação; Aspectos culturais; Sucesso; Empreendedorismo; Ecosystem or innovation clusters; Cultural aspects; Success; Entrepreneurship; ACCNPQ::Ciências Sociais Aplicadas::Administração